Increased IL-25 levels in the peritoneal fluid of patients with endometriosis. (April 2016) - Bungum, Helle Folge; Nygaard, Uffe; Vestergaard, Christian; Martensen, Pia M.; Knudsen, Ulla Breth
Highlights: Significantly higher levels of IL-25 in the PF of women with endometriosis. IL-25 levels did not correlate to age or stage of endometriosis. Menstrual phase or hormonal status was not correlated to IL-25 levels. IL-25 might hold a potential as a diagnostic tool for endometriosis. Abstract: Previous studies have indicated a higher prevalence of allergic disease among women with endometriosis. It is already well established that type 1 allergies develop in a Th2 cytokine environment. Recent studies have shown, however, that IL-25 induces a Th2 development of naive T lymphocytes and is central in the Th2 response. The aim of this case-control study was to investigate the presence of IL-25 in the peritoneal fluid of women suffering from endometriosis. PF was obtained both from women undergoing laparoscopic surgery due to endometriosis (25 cases) and from women wanting sterilisation (19 controls). IL-25 levels were then investigated by ELISA. Women with endometriosis showed significantly higher levels of IL-25 in their PF ( p  = 0.019) compared to controls. IL-25 levels did not correlate with the stage of endometriosis. Both Th2-cells and mast cells express IL-25, which could favor the development of allergies by perpetuating a hypersensitivity reaction. Further, IL-25 may also hold a role as a diagnostic tool.